1993
DOI: 10.1136/emj.10.2.117
|View full text |Cite
|
Sign up to set email alerts
|

A case of methaemoglobinaemia.

Abstract: SUMMARYMethaemoglobinaemia is rare but should be considered in cases of cyanosis unresponsive to oxygen therapy. An example of this is given involving the accidental ingestion of Amyl Nitrite. CASE REPORTA 20-year-old girl attended the accident and emergency department following a collapse. She was alert and orientated, but complained of headache. Her blood pressure was 80/40 mmHg. Her most striking feature was a blue-grey discolouration of her skin. Oxygen therapy made no difference to her appearance, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Increased formation of MetHb inhibits oxygen transport in blood, and its saturation leads to ischemia, cyanosis, and irreversible damage in the tissues and ultimately to mortality [32]. Gonchar et al [4] demonstrated that MetHb formation increased in rat blood 50 min after injection of NaNO 2 60 mg/kg, s.c.…”
Section: Discussionmentioning
confidence: 99%
“…Increased formation of MetHb inhibits oxygen transport in blood, and its saturation leads to ischemia, cyanosis, and irreversible damage in the tissues and ultimately to mortality [32]. Gonchar et al [4] demonstrated that MetHb formation increased in rat blood 50 min after injection of NaNO 2 60 mg/kg, s.c.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports of methaemoglobinaemia caused by recreational abuse or inadvertent ingestion of liquid nitrites (usually amyl or butyl nitrite) 29–35 . Methaemoglobinaemia is a disorder affecting the oxygen‐carrying capacity of haemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports of methaemoglobinaemia caused by recreational abuse or inadvertent ingestion of liquid nitrites (usually amyl or butyl nitrite). [29][30][31][32][33][34][35] Methaemoglobinaemia is a disorder affecting the oxygen-carrying capacity of haemoglobin. The acquired syndrome occurs in the presence of an oxidant, usually drug-induced, which converts the ferrous (Fe ++ ) heme moiety of haemoglobin to the ferric (Fe +++ ) form.…”
Section: Nitritesmentioning
confidence: 99%
“…Subsequent to this, there have been 25 reports of methaemoglobinaemia secondary to inhalation and/or ingestion of volatile nitrites, with methaemoglobin concentrations of between 17.8% and 94% [2–21]. The majority of these cases survived, and a proportion were treated with methylthioninium chloride.…”
Section: Volatile Nitrite‐related Methaemoglobinaemiamentioning
confidence: 99%
“…The majority of these cases survived, and a proportion were treated with methylthioninium chloride. The cases where the individual survived are summarized in Table 2[1–21] and the three reported deaths are discussed in more detail later in this article [22–24]. For the interest of the reader, we have discussed three of the non‐fatal cases in more detail below.…”
Section: Volatile Nitrite‐related Methaemoglobinaemiamentioning
confidence: 99%